Manajemen Pengelolaan Lembaga Kesejahteraan Sosial dalam Membentuk Kemandirian Panti Pelayanan Sosial Anak - Mardiana, Mardiana (Islamic Management and Empowerment Journal, 2023)
The aim of this research is to find out how children's social welfare institutions are managed and the formation of independence at the Kumuda Putera Puteri Children's Social Services Home in Magelang City using descriptive qualitative research methods. The results of the research explain that the management of the Kumuda Putera Puteri social welfare institution applies planning management, organizing management, preparation/personnel management, direction management, coordination management and supervisory management. Meanwhile, forming independence is done by giving children confidence in managing daily activities, providing opportunities to organize in the orphanage, providing rewards and punishment, providing psychosocial needs, developing interests, talents, and temporary programs.